EVALUATION OF ENZYMATIC HYDROLYSIS APPLIED TO FISH BY-PRODUCT OIL THROUGH CHEMICAL PARAMETERS - MORONI SILVA, C.; GERALD LIMA, F.; FURTADO DA COSTA, K.; AMARAL RIBEIRO, V.; RIBEIRO LEITE, R.S.; PETENUCI, M.E.; NEVES GELINSKI, J.M.L.; GRACIANO FONSECA, G.; PRENTICE, C. (Italian Journal of Food Science, 2020)
Large amounts of fish waste are produced by the fish processing plants. This waste could be used to obtain high value-added products, such as long chain polyunsaturated fatty acids. Thus, the aim of this work was to evaluate the enzymatic hydrolysis of low commercial value crude fish oil through chemical parameters. Crude fish oil was obtained from mixed fishmeal production and was chemically refined. Candida rugosa lipase AY "Amano" 30 was utilized to catalyze the enzymatic hydrolysis. The acidity index, iodine value, saponification index and peroxide value were used to characterize the samples studied. The chemical refining process yielded 62.75% and improved the quality of crude fish oil by reducing the acidity index around 91%. The best results of hydrolysis degree (23.45%) and iodine value (120 g I2 g-1) were obtained at 45ºC after 6 h of lipase action. The iodine value of crude oil was not affected by processing, indicating that the nutritional quality was preserved in the refined oil. Despite the hydrolysis process showed good results, it was not sufficient to concentrate the unsaturated fatty acids of refined oil, as indicated by the iodine value.